Institutional Strengthening of Village-Owned Enterprise Legal Entities as a Manifestation of Village Sustainable Development Goals - Budi Ambarini, Nur Sulistyo; Yamani, M; Andika, Tri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 2 (2023), 2023)
This study aims to analyze the arrangement of Village Owned Enterprises in Indonesia and their management in realizing village Sustainable Development Goals. Village Owned Enterprises as socio-economic institutions in villages can realize sustainable development goals in villages. However, most of the existing Village-Owned Enterprises have yet to function optimally in driving the village economy. This is doctrinal legal research with legal, conceptual, and philosophical approaches. This method seeks to discuss the arrangement of Village-Owned Enterprises in Indonesia and the importance of institutional strengthening of Village-Owned Enterprises as socio-economic institutions with legal status in realizing the Sustainable Development Goals in Villages. The institutional arrangement and strengthening of Village-Owned Enterprises, apart from legal and economic aspects, also require social capital support. Rural local customs in the form of local wisdom and customary law norms that are still relevant can be social capital for the institutional strengthening of Village-Owned Enterprises. Based on local wisdom and customary law norms, the institutional management of Village Owned Enterprises can be optimal in realizing the goals of village sustainable development.